A NSFD Discretization of Two-Dimensional Singularly Perturbed Semilinear Convection-Diffusion Problems - Kehinde, Olawale O.; Munyakazi, Justin B.; Appadu, Appanah R. (Frontiers in Applied Mathematics and Statistics, 2022)
Despite the availability of an abundant literature on singularly perturbed problems, interest toward non-linear problems has been limited. In particular, parameter-uniform methods for singularly perturbed semilinear problems are quasi-non-existent. In this article, we study a two-dimensional semilinear singularly perturbed convection-diffusion problems. Our approach requires linearization of the continuous semilinear problem using the quasilinearization technique. We then discretize the resulting linear problems in the framework of non-standard finite difference methods. A rigorous convergence analysis is conducted showing that the proposed method is first-order parameter-uniform convergent. Finally, two test examples are used to validate the theoretical findings.